Relationship of the Structure and the Effective Diffusion Properties of Porous Zinc- and Copper-Containing Calcium Phosphate Coatings; Inorganic Materials: Applied Research; Vol. 9, iss. 3 - Nazarenko N. N. Nelli Nikolaevna; Knyazeva A. G. Anna Georgievna; Komarova E. G. Ekaterina Gennadjevna; Sedel'nikova M. B. Maria Borisovna; Sharkeev Yu. P. Yury Petrovich (2018, 2018)
Title screen